CARBON ACCOUNTING APPLICATION IN THE AGRICULTURAL PRODUCTS SECTOR WITHIN THE SCOPE OF CLIMATE CHANGE, SUSTAINABILITY AND ACCOUNTING STANDARDS - Kiritoglu, Cenk (International Scientific Journal Vision, 2025)
A series of ecological and environmental problems driven by global warming has become an issue that individuals must confront, while for businesses it represents a significant source of risk and cost. In the face of the global climate crisis, the agricultural sector is both a major source of greenhouse gas emissions and a strategic sector with considerable carbon sequestration potential, which is instrumental in combating climate change. Accordingly, the implementation of accurate, transparent, and reliable carbon accounting practices has become imperative in the agricultural products sector. This article comprehensively addresses the theoretical foundations, implementation methodologies, and reporting requirements of carbon accounting in the agricultural products sector, within the context of climate change, sustainability, and accounting standards. Through a sustainability report and a carbon accounting case study, the article provides guidance to investors in the agricultural sector concerning costs and risks.In Turkey, the Turkish Sustainability Reporting Standards (TSRS), which entered into force on December 29, 2023, have made the reporting of sustainability and climate-related information mandatory for enterprises meeting certain criteria. Accordingly, agricultural enterprises are required to account for their carbon emissions in line with the Turkish Accounting Standard 41 (TAS 41) – Agriculture and to carry out integrated reporting in compliance with TSRS 2 – Climate-Related Disclosures.The research revealed that particularly small enterprises in the agricultural sector are not adequately prepared for the implementation of sustainability standards and carbon accounting practices due to deficiencies of capital, technology, infrastructure, and capacity. Deficiencies observed in carbon emission calculations, inconsistencies between Tax Accounting and TAS 41, and the lack of necessary accounts for carbon accounting in the Uniform Chart of Accounts indicate that comprehensive regulations in accounting and tax systems are needed to ensure the successful implementation of the process initiated by the Climate Law No. 7552.